2017
DOI: 10.1111/jog.13234
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal management of severe pelvic organ prolapse in nulliparous women

Abstract: Management of nulliparous advanced POP poses significant challenges with regard to uterine preservation, future pregnancy and childbirth. Conservative management with pessary insertion should be offered followed by surgical correction. Reconstructive surgery with mesh may improve prolapse symptoms objectively and subjectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The study of Lo et al reported on 1,275 surgically managed women with a prolapse of POPQ stage ≥3. In this large sample from one Taiwanese center, collected between 2005 and 2015, 8 women were nulliparous (0.55%) [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Lo et al reported on 1,275 surgically managed women with a prolapse of POPQ stage ≥3. In this large sample from one Taiwanese center, collected between 2005 and 2015, 8 women were nulliparous (0.55%) [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, rare cases of POP, linked to other factors, have been reported in nulliparous women [ 4 – 7 ]. The overall rarity of POP in nullipara is confirmed by the low proportion of POP surgery in this group (0.55–1.5%) [ 5 , 8 ], which may be explained by its absence or the presence of low pelvic organ prolapse quantification (POPQ) stages (0, 1, and 2) on clinical examination up to 60 years of age [ 9 ]. A number of earlier studies have shown that clinical POP with symptoms in nulliparous women <60 years occurs in less than 2–3% [ 9 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first one determines the impact of dysfunction in an individual and the second one quantifies the degree of PoP [21,27]. These two instruments can also be found in numerous studies [23,26,[28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Complications of vaginal pessaries include persistent expulsion, bleeding, ulcers, vaginal discharge, and fistulas and between 16-45% of women are unable to sustain long-term use (Liu & Lee 2017;Robert et al 2017;Yimphong et al 2017). Surgical interventions are prescribed for around one in ten women with POP but success rates following surgery are variable, dependent on the location and degree of prolapse and the nature of the surgical intervention (Kurkijarvi et al 2017;Lo et al 2017;Lowenstein et al 2017;Schiavi et al 2017). Satisfaction post-surgery is reported to decrease over time, with reduced quality of life and poorer sexual function being commonly reported 12 months post-surgery (Rahkola-Soisalo et al 2017;Tyagi et al 2017).…”
Section: Introductionmentioning
confidence: 99%